Survey, experimental and simulation-based approaches for understanding the risks of yield losses and mycotoxin contamination to improve regional management of Fusarium head blight in wheat - Duffeck, Maíra Rodrigues (2020)
Fusarium head blight (FHB) is a major disease of wheat, barley and other small grain cereals due to contamination of grain with mycotoxins produced by the pathogenic fungus. The first chapter focused on quantifying and assessing the spatial variability of mycotoxins presented in commercial wheat grain samples in Brazil, as well as evaluating the accuracy and precision of immunoassay kits compared with the reference chromatographic method. The mycotoxins deoxynivalenol (DON), zearalenone (ZEA) and ochratoxin A (OTA) were quantified in wheat grain samples collected in 2015 across 78 locations in the states of Paraná, Rio Grande do Sul, and São Paulo. The OTA mycotoxin was not found in the samples by both methods. The overall mean levels of DON and ZEA quantified by the reference method was 795.2 μg kg​ -1 and 79.78 μg kg​ -1​ , respectively. The ZEA levels estimated by the immunoassay agreed with the reference method, while DON levels were overestimated. In the second chapter, I employed a model-based approach to estimate the relative wheat yield losses due to FHB, and predict economic scenarios for fungicides application. First, a ​ review of the literature on fungicide efficacy evaluated in Brazilian field trials was conducted to obtain FHB-yield data and explore their relationship following a meta-analytic method. ​ Based on the median of maximum yields across trials, the studies were grouped into low (​ Yl ≤ 3,631 kg ha​ -1​ ) or high (​ Yh > 3,631 kg ha​ -1​ ) baseline yields. Population-average intercepts, but not the slopes, differed between ​ Yl (2,883.6 kg ha​ -1​ ) and ​ Yh (4,419.5 kg ha​ -1​ ) baselines yields and the damage coefficients were 1.60%​ -1 and 1.05%​ -1​ , respectively. Our modeling of yield losses due to FHB in a 28-year period (1980 to 2007) showed that the magnitudes and trends obtained in this study were in general agreement with literature reports. The profitability of fungicide spray tended to increase in general after the 1990s, when a single fungicide spray (but not often two sprays) was more likely to pay off. In the third chapter, 421 ​ Fusarium isolates from naturally FHB-infected spikes of different small grain hosts obtained across Pennsylvania (PA) in 2018 and 2019 were identified by molecular methods, using a FGSC-specific primer. The toxigenic potential of this isolates, ​ as well as an additional set of 77 ​ F. graminearum isolates from overwintering crop residues during the Winter 2012​ , were determined with a ​ multiplex PCR assay that amplified portions of the ​ TRI3 and ​ TRI12 genes. A subsample of 31 ​ F. graminearum isolates, 16 of the 3ADON and 15 of the 15ADON type, were assessed for their reproductive fitness and sensitivity to triazole-based fungicides. Results showed that ​ F. graminearum accounted for 97% of the FHB pathogen profile in PA, wherein 95.7%, 3.7%, and 0.6% of these isolates possessed the 15ADON, 3ADON and NIV trichothecene genotype. The frequency of the toxin types did not differ among sampled hosts nor years. The two genotypes could not be differentiated for most of the saprophytic traits based on multivariate analysis. All isolates were sensitive to tebuconazole and metconazole fungicides ​ in vitro ​ . The results obtained in these studies contribute to advance knowledge of an important disease to both countries and may serve as a basis to improve regional management strategies. Keywords: ​ Triticum aestivum ​ . ​ Fusarium graminearum ​ . Trichothecenes. Deoxynivalenol. meta-analysis.